Properties of anaerobic bacteria from ferrosphere crucial for biofilm development - Tkachuk, Nataliia; Zelena, Liubov; Mazur, Pavlo (Ecological Questions, 2021)
The purpose of this study was the investigation of biofilm-forming, hydrophobic, sulfidogenic and aggregative properties of sulfate-reducing bacteria Desulfovibrio oryzae strains in monocultures and associations with organic acid-producing bacteria Anaerotignum propionicum. Studies of biofilm formation on polypropylene surface by strains were carried out by a biofilm assay (indirect measurement of bacterial biofilm biomass by crystal violet adsorption/desorption), hydrogen sulfide production was determined by iodometric titration, aggregation - by aggregation test, hydrophobicity - by salt aggregation test. It was found that the studied strains of D. oryzae NUChC SRB1 and NUChC SRB2 are highly adhesive, have high sulfidogenic, aggregation and hydrophobic properties in the complete Postgate’s medium (with Fe2+). During the cultivation of the studied strains of D. oryzae with A. propionicum NUChC Sat1, a significant increase in aggregation (both in complete medium and without Fe2+) and hydrogen sulfide production by sulfate-reducing bacteria were observed. These properties indicate the potentially high biodegradable activity of D. oryzae monocultures NUChC SRB1 and NUChC SRB2 and their associations with A. propionicum NUChC Sat1. The observed increase in the sulfidogenic activity of D. oryzae in association with A. propionicum promotes the corrosion hazard of the studied bacterial association.